Self Concept and Future Orientation in Career Maturity: Konsep Diri dan Orientasi Masa Depan dalam Kematangan Karier - TARISHA JAFNA DIAH ZAHRANI; Nurfi Laili (Academia Open, 2025)
General Background: Career maturity represents a crucial developmental task for vocational high school students transitioning to higher education or the workforce. Specific Background: Many students experience uncertainty in career planning due to unclear self-understanding and vague future orientation, which may hinder structured career decision-making. Knowledge Gap: Previous studies have predominantly examined self-concept and future time perspective separately, with limited research integrating both variables simultaneously in explaining career maturity among vocational students. Aims: This study aims to examine the relationship between self-concept and future time perspective with career maturity among twelfth-grade students of SMK X Sidoarjo. Results: Using a quantitative correlational design involving 264 students selected through proportionate random sampling, the findings reveal significant positive relationships between self-concept and career maturity, as well as between future time perspective and career maturity. Multiple regression analysis indicates that both variables simultaneously contribute significantly to career maturity. Novelty: The study offers an integrated correlational model combining two internal psychological constructs within a single framework for vocational students. Implications: The findings underline the importance of strengthening self-understanding and structured future orientation through school-based career guidance programs to support adaptive career planning and decision-making. Keywords: Self-Concept, Future Time Perspective, Career Maturity, Vocational High School Students, Career Development Key Findings Highlights: Internal psychological factors jointly explain substantial variance in students’ vocational readiness. Positive self-evaluation aligns with structured planning and autonomous decision processes. Long-term goal orientation relates to systematic exploration of occupational pathways.